The effect of contemporary political scenerio in Malaysia: the change in attitude towards mainstream newspaper reading habit / Izatul Azzuar Ibrahim, Dahlia Permid and Mohd Hazry Osman - Ibrahim, Izatul Azzuar; Permid, Dahlia; Osman, Mohd Hazry (Faculty of Business and Management, 2001)
Before we go any further, it is important to state that this project paper is part of the subject requirements for the Research Methodology Subject (MGT 368) to completing the Diploma Business Studies program. In the other hand, this project paper is designed to achieved several objectives, there are: